Losartan for the nephropathy of sickle cell anemia: A phase‐2, multicenter trial. Issue 9 (19th July 2017) - Quinn, Charles T.; Saraf, Santosh L.; Gordeuk, Victor R.; Fitzhugh, Courtney D.; Creary, Susan E.; Bodas, Prasad; George, Alex; Raj, Ashok B.; Nero, Alecia C.; Terrell, Catherine E.; McCord, Lisa; Lane, Adam; et al.
Abstract: Nephropathy is a common and progressive complication of sickle cell anemia (SCA). In SCA mice, we found that hyperangiotensinemia in the absence of hypertension underlies nephropathy, and its downregulation by losartan, an angiotensin‐II‐receptor‐1 blocker, reduced albuminuria and progression of nephropathy. Therefore, we performed a phase‐2 trial of oral losartan, given for 6 months, to explore whether it reduced albuminuria in children and adults with SCA. Participants were allocated to groups defined by class of baseline urinary albumin‐to‐creatinine ratio (UACR): no albuminuria (NoA), microalbuminuria (MicroA), and macroalbuminuria (MacroA). The primary endpoint was a ≥25% reduction UACR from baseline. There were 32 evaluable participants (mean age 24 years; NoA = 14, MicroA = 12, MacroA = 6). The primary endpoint was met in 83% of the MacroA group ( P < 0.0001) and 58% of the MicroA group ( P < 0.0001). Median fold‐change in UACR was −0.74 for MacroA and −0.46 for MicroA. In MacroA and MicroA, UACR classification improved in 50% but worsened in 11%. Urine osmolality and estimated glomerular filtration rate (eGFR) did not change significantly. Losartan was discontinued in three participants [leg cramps, N = 1; decline in eGFR >25% (142➝104 mL/minute/1.73 m 2 ), N = 1; rise in serum creatinine >50% (0.2➝0.3 mg/dL), N = 1]. Albuminuria was associated with diastolic dysfunction and impaired functional capacity, although cardiopulmonary status was unchanged after 6 months of losartan therapy. In summary, losartan decreased urinary albumin excretion in most participants with albuminuria. Those with macroalbuminuria had the greatest benefit. This study forms the basis for a phase‐3, randomized, placebo‐controlled trial of losartan for the nephropathy of SCA.